Ammi analysis of genotype × environment interaction and stability of sesame genotypes - Singh, Bhagwat; Bisen, Rajani (Bangladesh Journal of Botany, 2020)
The additive main effects and multiplicative interaction (AMMT) model for seed yield of 60 varieties of sesame per plant detected significant effects of the genotypes (17.87% sum of squares (SS)), environments (14.15% SS) and genotype × environment interaction (67.99% SS). The model also extracted two significant interaction principal component analysis (IPCA) with a total of 79.9% SS and 67.8% corresponding degrees of freedom. Genotype TMV-7 (17.308 g/plant) followed by N-8 (13.994 g/plant) had the highest average yield which was much greater than the grand mean (10.976 g/plant) and declared as area specific adapted genotypes. Environments El, E2 and E4 were unfavorable while E3 is the most suitable as indicated by high mean value of IPCA 1 and low value of IPCA 2.